Ethnopedagogical traditions of family education in Kosach-Dragomanov family in courses of educational disciplines «History of pedagogy» and «Theory and methodology of education» - Yaroshchuk, Liliya (Berdyansk State Pedagogical University, 2022)
The purpose of the study is to reveal the ethnopedagogical traditions of education in the Kosach-Dragomanov family in terms of courses of educational disciplines «History of pedagogy» and «Theory and methodology of education» in the conditions of distance learning. The article proves that the dominants of the upbringing of children in the Kosach-Dragomanov family were cultural, patriotic, spiritual, moral, mental, labor and religious education; the ethnopedagogical potential of the family accumulates spiritual, moral, cultural, national, mental, aesthetic, emotional, labor education through the cultivation of the Ukrainian mentality, in respect of the ethnopedagogical traditions of the Ukrainian people. It is proved that the successful assimilation of the achievements of the ethno-pedagogical familial experience by students, the acquisition of the highest spiritual and moral qualities of the individual is facilitated by audit and practical work: in classes on the theory and methodology of education, the history of pedagogy, the preparation of abstracts, research and search design, Internet quizzes, flash mobs. For example, now we are forced to study remotely, so within 25 days the online project of the Department of Pedagogy of Berdyansk State Pedagogical University «Paths of Pedagogical Heritage of Lesia Ukrainka» took place on the occasion of the 150th anniversary of her birth. Every day students of the Faculty of Psychological and Pedagogical Education and Arts introduced Lesia Ukrainka to poetry for the youngest in different formats: read poems, sang songs on the words of poets, painted portraits.
Keywords: ethnopedagogical tradition; upbringing of the children; family; experience; educational process; distance learning